EXPERIENCE OF APPLICATION OF COMPOSITIONS WITH S-METHYLMETHIONINE SULFONIUM CHLORIDE (VITAMIN U) FOR TREATMENT OF PERIODONTITIS - Yu.V. Sulym (Український стоматологічний альманах, 2018)
The study examines the effectiveness of treatment of periodontitis using gel and films containing Smethylmethionine sulfonium chloride on collagen and synthetic substrates.